LANNA MUSIC: ETHNOMUSICOLOGY OF THE ETHNOMUSICOLOGIST - Somchandra, Songkran (Mahidol Music Journal, 2023)
This research aims to study the concept and factor of the Lanna musical epistemology by the ethnomusicologist. The musicological and ethnomusicological method was conducted based on documents between 2500-2550 BE, interviews the music scholars who studied Lanna music at that time. The contributing to Lanna musical knowledge as well as academically was influenced by the rise of anthropological studies in the Cold War period. The American’s ethnomusicologist began their studied the music of northern Thailand with anthropological views. The regions musical studies were influenced by American’s educational concepts especially folklore-a studies music as a local wisdom. The data collecting, also the province’s cultural center was established and organized the musical seminars. However, the studies music with ethnomusicological views was began by music scholars who graduated from oversea universities. Before the establishment of ethnomusicology program in Thailand, they conducted research with regionalism, musical characteristic. The growing of music education program in the Teacher Colleges (currently, Rajabhat University), the College of Dramatic Arts, and the rise of localism in 2530 B.E. was influenced to the successfully of the lanna musical knowledge making. Although, Lanna's musical knowledge concentrating on Chiang Mai musical culture area, and distribute to other cultural areas since 2550 B.E. However, the central scholar who studied Lanna music outside Chiang Mai, views on regional music as folk music-not according to classical music. Utilizing the concept of Thai musicology which can be referred to as an internal colony. It's still a question of discussing the status of Lanna musical knowledge, in particular the use of contemporary anthropological and sociological theories to explain this phenomenon.